A competitive precision CRISPR method to identify the fitness effects of transcription factor binding sites - Pihlajamaa Päivi; Kauko Otto; Sahu Biswajyoti; Kivioja Teemu; Taipale Jussi (Nature Portfolio, 2022)
Here we describe a competitive genome editing method that measures the effect of mutations on molecular functions, based on precision CRISPR editing using template libraries with either the original or altered sequence, and a sequence tag, enabling direct comparison between original and mutated cells. Using the example of the MYC oncogene, we identify important transcriptional targets and show that E-box mutations at MYC target gene promoters reduce cellular fitness. A competitive CRISPR method discovers targets and phenotypic effects of the MYC oncogene.